Linear Regression Algorithm the Effect of Game Time on Students' Reading Interest - Ramadhan, Said; Novriyenni; Prahmana, I Gusti (Yayasan Kita Menulis, 2024)
Education plays an important role in shaping an individual's character and abilities, with students' interest in reading as the main foundation for intellectual development and critical thinking skills. However, in today's digital age, there has been an alarming decline in students' interest in reading, who are more interested in spending their free time playing games than reading. The development of information technology and digital entertainment such as smartphones, tablets, and computers has changed students' habits in utilizing their free time. Playing games is the main choice, while reading interest is marginalized, which has a negative impact on students' literacy skills. The decline in reading interest has serious implications, especially in Indonesia, where the Human Development Index (HDI) in the field of education is still low compared to neighboring Malaysia. This low interest in reading is influenced by the lack of reading habits from an early age and unequal access to education. Good reading skills not only affect academic achievement but also the development of critical, analytical, and creative thinking skills. This study aims to understand the factors that affect students' interest in reading, especially the influence of game time. The Simple Linear Regression method was used to analyze the relationship between game play time and students' reading interest, which provided valuable insights for educators and parents in designing effective educational strategies. The study focused on SMP Negeri 7 Binjai and used a linear regression method to analyze data on students' reading and gaming habits. The results of the study show that excessive game playing time, an average of 9 to 10 hours per day, has an impact on increasing and decreasing students' interest in reading. This data was analyzed using the RapidMiner application, which showed a correlation between playing games and students' reading interest.